The Effect of Ni Additions on the Microstructure and Castability of Low Si Added Al Casting Alloys. (2015) - Cho, Y.H.; Kim, H.W.; Kim, W.; Jo, D.A.; Lee, J.M.
Abstract: The addition of Ni up to 1 wt.% was made to an Al-1Si-1Fe alloy and its influence on the microstructure and castability was investigated. Fe-rich intermetallics present in the Al-1Si-1Fe alloy were dramatically refined by the Ni addition in excess of 0.5 wt.%, changing the morphology from a plate-like to a fine fibrous form. The alloys exhibit the maximum fluidity length at 0.5 wt.%Ni whilst hot tearing tendencies increased when increasing the Ni contents.